FAKTOR EKSTRINSIK YANG MEMPENGARUHI MOTIVASI BELAJAR SISWA KELAS IV SEKOLAH DASAR SE-GUGUS 2 KECAMATAN SAIL PEKANBARU - Ibrahim Musab; Gustimal Witri (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
The research was motivated by the low motivation of grade IV elementary school students. The study aims to determine extrinsic factors that influence the learning motivation of fourth-grade students in Gugus 2 Sail District Pekanbaru City. This type of research is quantitative descriptive research. The research sample consisted of 149 students. The data collection technique used is the questionnaire technique. The data analysis technique uses descriptive statistics. The results showed that extrinsic factors that affect student learning motivation at 8.26% were influenced by learning methods, 10.02% were influenced by teacher relations with students, 10.20% were influenced by student relations with students, 11.22% were influenced by discipline school, 8.61% influenced by learning tools, 10.93% influenced by school time, 10.70% influenced by learning standards above size, 10.66% influenced by building conditions, 10.20% influenced by curriculum, 9, 21% is influenced by homework. The conclusions of the study show that extrinsic factors that influence the learning of fourth-grade students of Gugus 2 Sail District Pekanbaru City is school discipline.